PENGARUH SERVICESCAPE TERHADAP KEPUASAN PENGGUNA JASA (Studi Kasus Pada Kantor Imigrasi Kelas I Malang) - Vivin Muarifah (Universitas muhammadiyah malang, 2017)
This study aimed to investigated the impact of servicescape on services user satisfaction at malang’s immigration office class 1. The analytical method used is multiple regression analysis. This research was conducted by distributing questionaires to 100 respondents at malang’s immigration office class 1 by using accidental sampling technique. Dimensions of servicescape that used in this study are ambient condition, spatial layout and functionality, signs, symbols, and artifacts, and social. Results of the analysis shows that dimensions servicescape have influence on services user satisfaction either simultaneously or partially